Electronic Tax Filing System and Compliance among Small and Medium-Sized Enterprises in Lagos State, Nigeria - Salawu, Mary Kehinde; Adigun, Omotoyosi Aminat; Lawal, Quadri Adebayo; Olaleye, Jelili Adediran (International Journal of Economics and Financial Issues, 2024)
The study examined the effect of the adoption of an e-tax filing system on SMEs compliance. This was with a view to providing information on the compliance of SMEs with electronic tax filing systems in Lagos State. The study employed a descriptive survey research design, targeting a population of 91,097 SMEs. Taro Yamane’s formula was used to obtain a sample of 398 SMEs. Data were collected through well-structured questionnaires and analyzed using ordinal logit regression techniques. The study showed that factors such as performance expectancy, effort expectancy, and e-tax filing awareness have a positive significant influence on SMEs compliance in Lagos State. The study concluded that the electronic tax filing system positively impacted tax compliance of SMEs in Lagos State. The study recommended that tax authorities should enhance the performance and effort expectancy of the e-tax filing system in Lagos State by addressing technical issues, streamlining the filing process, and improving user interface design.